Los talleres básicos de la Universidad de Lima: algunas reflexiones en torno a los procesos de enseñanza-aprendizaje - Fabbri García, Martín (2015)
This article was prepared by a group of teachers of the courses of Architectural Project I and II from the University of Lima. It aims to address the issue of organizing the teaching-learning process in basic design workshops proposing some reference points from the analysis of the results of the university in these first 4 years of academic work. The 3 phases of the workshop process that are the step of motivation or creative drive, the process of design and evaluation are proposed.